Young professionals' housing affordability through housing preferences in Kuala Lumpur and a review on the means-end chain model - Sohaimi,, Nor Suzylah; Abdullah, Alias; Shuid, Syafiee; Ahmad Sarkawi, Azila (Malaysian Institute of Planners, 2017)
In a broad-spectrum, housing affordability issue is interrelated to young professional's well-being. However, this paper deliberated on young professional's housing preference in affordability context by taking into account some attributes of housing preference criteria. Data was obtained through questionnaire survey among 50 respondents aged between 25 and 35 years old and working in various professional fields in Kuala Lumpur. Descriptive analyses were then undertaken on the data from the survey. The study found that security criterion is the highest priority in housing preferences among the respondents. Having Wi-Fi is the second most important criterion. Additionally, this paper also provides a conceptual review on the Means-End Chain mode